Understanding voluntary pro-environmental behavior among colleagues: roles of green crafting, psychological empowerment, and green organizational climate - Zafar, Hina; Tian, Feng; Ho, Jo Ann; Roh, Taewoo; Latif, Badar (John Wiley and Sons, 2024)
A concerning surge in pollution has drawn increased attention to sustainability efforts. The lack of environmentally conscious human behavior contributes significantly to environmental degradation. This research explores the impact of perceived colleague support towards the environment (PCSE) as a catalyst for promoting employees' green initiatives. Underpinned by the conservation of resources (COR) theory, the study reveals a sequential chain mediation model, wherein PCSE initiates a process leading to voluntary pro-environmental behavior (VPEB) among employees, facilitated by green crafting (GC) and a supportive green organization climate (GOC). Additionally, the study examines the moderating role of psychological empowerment (PE) on the relationship between GC and GOC. Data were collected at two-wav points with a 2-week gap from the Pakistani textile sector. Results indicate that GC and GOC serially mediate the relationship between PCSE and VPEB of employees. Furthermore, the results support the mediation of GOC between PCSE and VPEB. However, the results did not support the moderating impact of PE. The study discusses important theoretical and practical implications for fostering green initiatives among employees.